The effect of nutrition education on nutrition‐related health outcomes of Aboriginal and Torres Strait Islander people: a systematic review. (29th June 2015) - Schembri, Laura; Curran, Johannah; Collins, Lyndal; Pelinovskaia, Marta; Bell, Hayley; Richardson, Christina; Palermo, Claire
Abstract: Objective: To determine the effectiveness of nutrition education on improving nutrition‐related health outcomes in Aboriginal and Torres Strait Islander people. Methods: Databases Medline, Cinahl, Scopus, ProQuest and ATSI Health were searched in September 2013 to identify nutrition education intervention studies in Indigenous Australian populations. Peer‐reviewed and grey literature with nutrition‐related biochemical or anthropometrical health outcomes were included in a qualitative comparative analysis. Results: Of 1, 162 studies identified from the search, six met inclusion criteria. Three studies were from a remote setting and three from an urban setting. Four of the six education interventions were shown to improve body mass index (BMI) and/or nutritional biochemical indicators. Components of the nutrition education interventions showing greatest effect included cooking skills workshops, group education sessions and store interventions. Community involvement in the program design was most strongly associated with a positive effect on BMI. Conclusion: Nutrition education had some effect in reducing biochemical and anthropometric risk factors for chronic disease in Indigenous Australians. Implications: Nutrition education can be considered as part of a range of strategies to improve nutrition‐related health for Aboriginal and Torres Strait Islander people. Further evidence is needed to strengthen this recommendation.